DESKRIPSI HASIL BELAJAR MATEMATIKA SISWA MELALUI PEMBELAJARAN DARING PADA POKOK BAHASAN BANGUN RUANG SISI DATAR - Abdul Wahab Abdullah; Novianita Achmad; Nada Chandra Fahrudin (Universitas Negeri Gorontalo, 2020)
This study aims to describe students' mathematics learning outcomes through online learning for the 2019/2020 academic year on the subject of flat-sided space geometry. This descriptive study was conducted at SMP Negeri 5 Paguyaman involving 28 students of class VIII as a sample selected using the purposive sampling technique. Data collection techniques in this study were tests in the form of multiple-choice questions and student response questionnaires. The results of the research that refer to the cognitive domain of the revised Bloom taxonomy by Anderson and Krathwohl show that the C1 cognitive domain is remembering, the ability of students to remember, recognize or know a concept of the material being asked in the questions given an average of 77.36% is in a good category. C2 cognitive domain is understanding; students' ability to understand the material on average 35.75% is in the poor category. C3 cognitive realm applies, on this indicator, students' ability to apply the formula to the questions given an average of 17.85% is in the poor category. C4 cognitive domain analyzes students' ability to analyze the average question is 39.70% who are in the poor category. With the average percentage of all cognitive domains, namely 45.71%, students' mathematics learning outcomes through online learning on the subject of flat-side space geometry is still in the low category, and learning using Facebook Messenger has not provided maximum results.